The Relationship of Physical Activity Level and Stress Levels in Pregnant Mothers - Amin, Choirul; Astuti, Yuni (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Introduction many expectant mothers are unaware of the best physical activities to engage in to reduce stressful situations. Stress situations have an impact on pregnant women's and unborn children's health. Purpose of this study was to examine the connection between pregnant women's levels of physical activity and stress in the Banguntapan 1 Public Health Center workplace. Methodology this study employed a cross-sectional study design and a quantitative methodology. At Banguntapan Health Center 1, a purposive sampling was conducted on 78 pregnant women. Findings according to the study's findings, there was no correlation between pregnant women's levels of stress and physical activity (p value = 0.296). Implication the majority of pregnant women had heavy physical activity because most pregnant women carried out daily activities such as before pregnancy such as carrying out daily activities such as before pregnancy and were still actively working or selling to meet their daily needs.